Assessment of the relationship of serum liver enzymes activity with general and abdominal obesity in an urban Bangladeshi population - Ali, Nurshad (Sci Rep, 2021)
Obesity is a global health concern because of its increasing trend both in developed and developing countries. A limited number of studies have evaluated the association of liver enzymes with both general and abdominal obesity in the general population; data for the Bangladeshi population are not available yet. This study aimed to assess the relationship of serum liver enzymes activity with both general and abdominal obesity in Bangladeshi adults. In total, 540 blood samples were obtained from the participants (388 males and 152 females) and analyzed for serum levels of ALT, AST, GGT, and ALP using standard methods. General obesity was defined as body mass index (BMI) ≥ 27.5 kg/m(2) and abdominal obesity was defined as waist circumference (WC) ≥ 90 cm in males and ≥ 80 cm in females. The relationship between liver enzymes and obesity was evaluated by multivariate logistic regression models. Overall, 58% of participants in the general obesity group and 55% of the participants in the abdominal obesity group had at least one or more elevated levels of liver enzymes. The prevalence of elevated liver enzymes was significantly higher in the obesity group compared to the normal BMI and WC groups (p < 0.05 for all cases). The mean level of serum ALT, AST and GGT were significantly higher in the obesity group than the normal BMI group (p < 0.05). In the WC groups, mean AST and GGT were significantly higher in the obesity group compared to the normal group (p < 0.05). In regression analysis, serum levels of ALT showed an independent and significant association with general obesity, whereas, serum GGT showed a significant association with both general and abdominal obesity. In conclusion, a high prevalence of elevated liver enzymes was observed among participants included in the present study. Of the four enzymes, serum GGT was independently associated with both general and abdominal obesity. Further studies are required to understand the complex relationship between liver enzymes and obesity in the general population.